Research on Restrictive Factors and Planning of Charging Piles for Electric Vehicles in the Park Based on the Interpretative Structural Model - Zhang, Chao; Zhao, Yihang; Zhao, Huiru; Wang, Qiang (Frontiers in Energy Research, 2022)
At present, the world is vigorously promoting the innovative development concept of "green development, park first", prompting the park to vigorously promote the construction of electric vehicle charging stations and charging pile projects. However, the development of the construction is not satisfactory due to a series of restrictive factors. Under this background, this paper studies the constraints of electric vehicle (EV) charging stations in the park and further studies the impact on the park planning. Firstly, this paper draws the constraints of charging piles in the park based on the field research. Then, the interpretive structural modeling (ISM) is adopted in this paper for in-depth analysis of the restrictive factors. Finally, the impact on the industrial park planning is analyzed as case study. The improved countermeasures provide a basis for the scientific planning and design of electric vehicle charging piles in industrial parks.